PEMANFAATAN ANDROID DALAM DUNIA PENDIDIKAN - Verawati, Verawati; Comalasari, Enny (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
This paper is in the form of a paper that aims to see the use of technology in the form of an Android cellphone in the world of Education. In the digital era, seeing the smallest events in the world can quickly be via mobile phones. The technological advancements that have arrived at Android phones make us able to grasp the world. Android can have a positive or negative impact depending on the use and utilization in everyday life, especially in the world of education. One form of technological advancements in Android phones is the playstore, which is one of the bridge programs to install other programs. One of the many programs to study the layout and provinces in Indonesia is the "Indonesia" program. This program allows us to study the location of the province by arranging puzzles so that learning is more fun and not monotonous. This program consists of three levels so that beginners can be done at the beginner stage. The "Indonesia" program can be used at every level of education. Android can be used and used directly on other materials.